Morphology, immunohistochemistry characteristics, and clinical presentation of microcystic urothelial carcinoma: a series of 10 cases - Wenjing Su; Wenwen Sui; Xiankui Cheng; Yuanyuan Zong; Yejun Qin; Fengyun Cui (BMC, 2023)
Abstract Background Microcystic urothelial carcinoma (MUC) is a rare variant of urothelial carcinoma with histological appearances similar to begin lesions. Thus far, approximately 50 cases have been reported. Here, we investigated the clinicopathological features of MUC. Methods Clinical data and paraffin-embedded tissue blocks were collected. Immunohistochemical staining and polymerase chain reaction-Sanger sequencing were performed to detect the phenotype and TERT mutation status of MUC, respectively. Results The mean patient age was 58.8 ± 14.5 years, with a male predominance (8:2). The pathological stage was T1 in one case, T2 in three cases, T3 in four cases, and T4 in two cases. Tumor metastases or death occurred in all five patients who were followed up within 1-3 years. Histological analyses revealed microcystic, tubular, cribriform, and occasionally cord-like structures, which generally lacked interstitial reactions. The lumens were empty, contained eosinophilic secretion, or were filled with mucin. The microcysts/tubules/cribriform patterns were lined by flat, cuboid, signet ring, or columnar types of epithelia. The cuboid, signet ring, and columnar types represented "glandular metaplasia" or glandular differentiation of urothelial carcinoma. Immunohistochemistry analyses revealed distinct co-expression patterns involving the luminal markers FOXA1 and GATA3, as well as the basal markers CK5/6 and CD44. All 10 cases exhibited a luminal phenotype according to the GATA3+/CK14- criterion, whereas nine cases exhibited a luminal phenotype according to the FOXA1+/CK14- criterion. The telomerase reverse transcriptase-C228T mutation was detected in seven cases. Conclusions MUC is a rare variant with a deceptively benign form of urothelial carcinoma, which is generally identified as a late-stage tumor with a poor prognosis. It exhibits distinct co-expression of luminal and basal markers, along with the TERT-C228T mutation.